Herbal preparations for cure and preventive care of phosphate nephrolithiasis - N. G. Chaban; L. M. Rapoport; A. A. Tsarichenko; T. M. Buslaeva (Тонкие химические технологии, 2015)
The work presents the results of a research on the effect of water extracts of herbal preparations on phosphate concrements of different phase composition taken in vitro from 56 patients. Interrelation between the composition of the extracts and the pH of urine was found. Recommendations on the selection of herbal preparations providing favorable conditions for the litholysis of phosphate concrements were given.